Early Middle Ordovician scolecodonts from the Argentine Precordillera: the oldest known polychaete jaws of South America (Ameghiniana, 2014)
A small scolecodont collection from the late Arenig of the San Juan Formation, Talacasto section, Argentine Precordillera, is described and discussed. Associated conodonts allow for a precise biostratigraphic record for global correlation (upper part of the Balioniodus navis Zone). Collected specimens represent the oldest known scolecodonts from South America and some of the oldest ones known worldwide. This study provides the first record of the common Paleozoic family Polychaetaspidae in South America and extends its geographic distribution.